Antioxidant activity of silver nanoparticles synthesized using Holothuria atra extract - Irwan Irwan; Mutia Ramadhaniaty; Eli Nurliza (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Sea cucumber (Holothuria atra) was used as a reducing and capping agent in the green synthesis process to produce silver nanoparticles (AgNPs). The antioxidant activity of the generated silver nanoparticles was then evaluated. Seacucumber extract was mixed with the AgNO3 solution and homogenized using a magnetic stirrer to create the silver nanoparticles. It was determined that silver nanoparticle production had occurred using a UV-Vis spectrophotometer. Before being examined for antioxidant activity, the generated nanoparticles were first given a characterizing using Fourier Transform Infra Red (FTIR) spectrometers. The maximum uptake was obtained at wavelengths of 440 cm-1 using a UV-Vis spectrophotometer. Functional groups that play a role in the synthesis of nanoparticles were -OH- C=O, and C-O groups. The free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) with an absorbance maximum (517 nm) was used for antioxidant properties. The antioxidant assay showed that Silver nanoparticles had higher antioxidant activity than sea cucumber extract alone, with an IC50 value of 4 ppm.Keywords:AntioxidantSeacucumberGreen SynthesisSilver NanoparticlesDPPH